Mitochondrial dysfunction-targeting therapeutics of natural products in Parkinson’s disease - He, Ting; Lin, Xiaoyan; Su, Anping; Zhang, Yujie; Xing, Zhichao; Mi, Li; Wei, Tao; Li, Zhihui; Wu, Wenshuang (Frontiers in Pharmacology, 2023)
Parkinson’s disease (PD), the second most common neurodegenerative disease worldwide, often occurs in middle-aged and elderly individuals. The pathogenesis of PD is complex and includes mitochondrial dysfunction, and oxidative stress. Recently, natural products with multiple structures and their bioactive components have become one of the most important resources for small molecule PD drug research targeting mitochondrial dysfunction. Multiple lines of studies have proven that natural products display ameliorative benefits in PD treatment by regulating mitochondrial dysfunction. Therefore, a comprehensive search of recent published articles between 2012 and 2022 in PubMed, Web of Science, Elesvier, Wliey and Springer was carried out, focusing on original publications related to natural products against PD by restoring mitochondrial dysfunction. This paper presented the mechanisms of various kinds of natural products on PD-related mitochondrial dysfunction regulation and provided evidence that natural products are promising to be developed as drugs for PD therapeutics.